Doxorubicine-Congestive Heart Failure-Increased Big Endothelin-1 Plasma Concentration: Reversal by Amlodipine, Losartan, and Gastric Pentadecapeptide BPC157 in Rat and Mouse - Martina Lovric-Bencic; Predrag Sikiric; Jadranka S. Hanzevacki; Sven Seiwerth; Dunja Rogic; Vesna Kusec; Gorana Aralica; Pasko Konjevoda; Lovorka Batelja; Alenka B. Blagaic (Elsevier, 2004)
Overall, doxorubicine-congestive heart failure (CHF) (male Wistar rats and NMRI mice; 6 challenges with doxorubicine (2.5 mg/kg, i.p.) throughout 15 days and then a 4-week-rest period) is consistently deteriorating throughout next 14 days, if not reversed or ameliorated by therapy (/kg per day): a stable gastric pentadecapeptide BPC157 (GEPPPGKPADDAGLV, MW 1419, promisingly studied for inflammatory bowel disease (Pliva; PL 10, PLD-116, PL 14736)) (10 μg, 10 ng), losartan (0.7 mg), amlodipine (0.07 mg), given intragastrically (i.g.) (once daily, rats) or in drinking water (mice). Assessed were big endothelin-1 (BET-1) and plasma enzyme levels (CK, MBCK, LDH, AST, ALT) before and after 14 days of therapy and clinical status (hypotension, increased heart rate and respiratory rate, and ascites) every 2 days. Controls (distilled water (5 ml/kg, i.g., once daily) or drinking water (2 ml/mouse per day) given throughout 14 days) exhibited additionally increased BET-1 and aggravated clinical status, while enzyme values maintained their initial increase. BPC157 (10 μg/kg) and amlodipine treatment reversed the increased BET-1 (rats, mice), AST, ALT, CK (rats, mice), and LDH (mice) values. BPC157 (10 ng/kg) and losartan opposed further increase of BET-1 (rats, mice). Losartan reduces AST, ALT, CK, and LDH serum values. BPC157 (10 ng/kg) reduces AST and ALT serum values. Clinical status of CHF-rats and -mice is accordingly improved by the BPC157 regimens and amlodipine. Keywords:: pentadecapeptide BPC157, big endothelin-1, doxorubicine-congestive heart failure, amlodipine, losartan